Increasing marine ecosystems conservation linking marine protected areas and integrated coastal management in southern Cuba. (1st October 2020) - Perera-Valderrama, Susana; Hernández-Ávila, Aylem; Ferro-Azcona, Hakna; Cobián-Rojas, Dorka; González-Méndez, Juliett; Caballero-Aragón, Hansel; Guardia-Llansó, Elena de la; Ramón-Puebla, Adonis; Hernández-González, Zaimiuri; Espinosa-Pantoja, Leonardo; Lara, Ariagna
Abstract: The southern archipelagos of Cuba comprise important ecosystems of mangrove, seagrass beds, and coral reefs of regional significance. Biodiversity and fisheries stocks in this area experienced a severe decline due to a combination of factors (overfishing, habitat degradation, climate change). This work presents the main impacts of the project "Southern Archipelagos", led by the National Center of Protected Areas of Cuba and funded by GEF, between 2009 and 2015 and the trends of the indicators of success. The project contributed to the conservation of marine biodiversity in Cuba through the creation of 12 new marine protected areas (MPAs). "Southern Archipelagos" facilitated the inclusion of the new and existing MPAs in Integrated Coastal Management Zones (ICMZs), thus contributing to buffering the impacts of productive activities and strengthening the integration between the conservation and productive sectors. Studies were conducted to characterize the MPAs and monitoring programs for priority species and ecosystems were implemented, increasing the knowledge available for decision-making about marine species and ecosystems in the region. To guarantee the financial sustainability of MPAs, a strategy for sustainable tourism was developed and a series of studies on the economic value of the goods and services offered by ecosystems were conducted. Different training programs for local leaders, MPAs workers and workers of productive sectors were organized. Sustainable productive alternatives were implemented in several communities diversifying the economic activities of local people. As a result, revenues from a representative sample of 12 MPAs of the project increased in the two currencies that are managed in Cuba. Graphical abstract: Image 1 Highlights: We present the main impacts of the Cuban project "Southern Archipelagos". The project promoted the creation of new MPAs. The MPAs were included in Integrated Coastal Management Zones. New information on biodiversity and its economic value was obtained. Integration strategies were developed with the productive sectors of tourism and fishing.